2019
DOI: 10.1177/2516103219829483
|View full text |Cite
|
Sign up to set email alerts
|

Do adolescents in care systematically under-report their mental health difficulties in population studies? A narrative review

Abstract: The present article reports findings of a narrative review of self- and carer-report mental health data that addressed the research question: Do adolescents who reside in statutory out-of-home care (OOHC) systematically underreport their mental health difficulties in population studies? A literature search was conducted to identify population studies of the mental health of older children and adolescents in OOHC that obtained self-report data. Studies were selected for review if mental health data were gathere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…Importantly, self‐reported measures should continue to be included as a part of mental health assessment practice. Recent research showed that CYP in residential care appeared to provide reliable self‐reported information on mental health difficulties (Tarren‐Sweeney, 2019). Third, some of the measures are lengthy (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, self‐reported measures should continue to be included as a part of mental health assessment practice. Recent research showed that CYP in residential care appeared to provide reliable self‐reported information on mental health difficulties (Tarren‐Sweeney, 2019). Third, some of the measures are lengthy (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Further research on this topic should ideally include adolescent clinical interviews and self-report measures, as well as caregiverreport measures. However, it is important to retain caregiver measures in any future study, given evidence that young people in OOHC systematically under-report their mental health difficulties in population studies (Tarren-Sweeney, 2019). A second possible study limitation is that BPD and C-PTSD cases were defined from items on broad-range mental health checklists, rather than instruments designed explicitly to measure BPD and C-PTSD diagnostic criteria.…”
Section: Limitations and Implications For Future Researchmentioning
confidence: 99%
“…Further research on this topic should ideally include adolescent clinical interviews and self-report measures, as well as caregiverreport measures. However, it is important to retain caregiver measures in any future study, given evidence that young people in OOHC systematically under-report their mental health difficulties in population studies (Tarren-Sweeney, 2019). A more definitive study of adolescent symptomatology should utilize multiple informants, including adolescent self-report.…”
Section: Study Limitationsmentioning
confidence: 99%